A system design approach for overcoming heat exchanger fouling bottlenecks - a study on a refinery preheat train - Abdul Manan, Zainuddin; Ying, Ronald Chieh Ling (Institusi Jurutera Kimia Malaysia, 2003)
Process fouling and the penalties associated with it in petroleum refinery, particularly in the crude preheat train, have been the subject of extensive research over the last 30 years. Periodic cleaning and temperature drop due to the fouling have resulted in productivity losses and increased energy consumption. A common approach to reduce cleaning downtime is the injection of effective antifoulants into crude oil stream. However, with the wide variation in crude oil composition and fouling mechanisms, the use of antifoulant alone can often be ineffective. Together with the use of antifoulant, a systems’ design approach was proposed in this study to remove process bottlenecks due to heat exchanger fouling in a petroleum refinery preheat train. The method calls for retrofit by over-designing the fouled exchangers. Retrofit has managed to prevent drastic temperature drop due to severe heat exchanger fouling and also due to the removal of the fouled heat exchangers for cleaning. In addition, retrofit has enabled the plant authority to maintain the targeted nominal production rate throughout the year. The project can potentially result in a total savings of $0.6milion in utility costs and in productivity increase. Economic analysis shows that a reasonable pay back period of within two years for the retrofit is achievable; indicating that retrofit is technically and economically feasible.